Assessing The Awareness and Perceptions of Muslim Entrepreneurs on The Benefits of Islamic Microfinance in The Philippines - Salic, Jawad Zacaria (IKONOMIKA, 2024)
Islamic banking is gaining popularity around the world as an alternative financial system that encourages ethical and socially responsible investing. The Muslim population in the Philippines accounts for a sizable share of the country's micro, small, and medium-sized enterprise (MSME) sector. However, due to a variety of problems, including a lack of understanding, limited access to Islamic Microfinance products, and insufficient regulatory frameworks, the adoption of Islamic financing among Muslim businesses remains low. The purpose of this study is to analyze Muslim entrepreneurs' awareness and perceptions of the benefits of Islamic Microfinance in the Philippines.A mixed-methods research strategy was used in the study, which combined quantitative and qualitative data collection methods. A survey questionnaire was distributed to selected Muslim entrepreneurs from diverse industries in the Philippines for the quantitative component. The poll measured their degree of awareness and understanding of Islamic finance, as well as their perceptions of the benefits of Islamic Microfinance and the factors that prevent them from utilizing Islamic Microfinance products. The qualitative component included in-depth interviews with selected respondents to acquire a better understanding of their experiences and perspectives on Islamic Microfinance.The study is important because it adds to the literature on Islamic Microfinance in the Philippines and has the potential to promote financial inclusion and economic development among Muslim communities. The study's findings shed light on the impediments to Islamic Microfinance adoption among Muslim entrepreneurs and influenced policy suggestions targeted at supporting the expansion of the Islamic finance industry in the Philippines. Furthermore, the conclusions of the study are applicable to other nations with considerable Muslim populations, particularly those with developing Islamic banking industry.The research's main outcome was a comprehensive investigation of Muslim entrepreneurs' awareness and attitudes of the benefits of Islamic finance in the Philippines. The study sought to provide empirical facts that may be used to inform the creation of policies and initiatives targeted at encouraging MSMEs in the country to use Islamic Microfinance products. Finally, the findings of the study contributed to the general growth and development of the Islamic finance industry in the Philippines, as well as to the promotion of financial inclusion and economic empowerment among Muslim communities.